REGIONAL AND SECTORAL DIFFERENTIATION OF SOLIDARY REPLACEMENT RATE IN ThE RUSSIAN FEDERATION - A. Solovyev; V. Popov; A. Shapoval; N. Nurieva; A. Kurmanov (Финансы: теория и практика, 2017)
The key problem of the sustainable development of the Russian pension system is important not only for the senior generations of the Russian citizens, but also for all segments of the country’s macroeconomy since the pension system within the market labor relations framework (unlike «the Soviet model») is a complex of financial interrelations between the employee and the employer with the direct participation of the state (represented by its financial and law enforcement authorities). The key indicator of the state pension system development level is the replacement rate. The article analyzes the results of the lost earnings replacement rate calculation with account for characteristics of insured persons and provides an analytical estimation of the conformity of the «Russian» replacement factor to the minimum international standards of social security.